The Effect of Mind Mapping Techniques on Writing Skill of Procedure Text for Students Class VII MTsN Model Sungai Penuh, Jambi Province, Indonesia - Ria Agustina (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2020)
This study aims to explain the influence of mind mapping techniques on writing procedure text skills. Theories that become the reference in this study are from Harsianti and Penguin, which are about the text of the procedure, the Deporter's opinion on the Mind Mapping Technique. This study uses a quasi-experimental method with factorial design. The populations in this study were all students of class VII MTsN Model Sungai Penuh, with the amount of the students are 122 students, with a total sample of 61 students consisting of 31 students of class VII.A and 30 students of class VII.B. The sampling technique is random sampling. Based on the analysis of the data obtained by the results of research that is mind mapping techniques are appropriate for learning in writing procedures for text writing procedures for students of class VII MTsN Model Sungai Penuh because with these techniques can improve students' skills in imagination and concentration as evidenced by the average value of class students the experiment was higher than the control class and statistical analysis showed F-count 108.9 > F table 20.60.